Insulin Downregulated the Infection of Uropathogenic Escherichia coli (UPEC) in Bladder Cells in a High-Glucose Environment through JAK/STAT Signaling Pathway - Chen-Hsun Ho; Shih-Ping Liu; Chia-Kwung Fan; Kai-Yi Tzou; Chia-Chang Wu; Po-Ching Cheng (Microorganisms, 2021)
Diabetic individuals have a higher incidence of urinary tract infection (UTI) than non-diabetic individuals, and also require longer treatment. We evaluated the effects of insulin pretreatment on the regulation of JAK/STAT transduction pathways in UPEC-infected bladder cells in a high-glucose environment. A bladder cell model with GFP-UPEC and fluorescent-labeled TLR4, STAT1, STAT3, and insulin receptor antibodies, was used to evaluate the relationship between insulin receptor signaling, TLR-4-mediated, and JAK/STAT-dependent pathways. Pretreatment with 20 and 40 µg/mL insulin for 24 h significantly and dose-dependently reduced UPEC infection in SV-HUC-1 cells. Additionally, the expression levels of STAT1 and STAT3 were downregulated in a dose-dependent manner. However, insulin receptor (IR) expression was not affected by insulin pretreatment. Our results showed that insulin-mediated reduction of UPEC infection in a high-glucose environment was not only due to the downregulation of JAK1/2 and phosphorylated STAT-1/3, but also because of the decreased expression of TLR-4 proteins and pro-inflammatory IL-6. Here, we demonstrated that insulin reduced not only UPEC infection in bladder epithelial cells, but also inhibited the JAK/STAT transduction pathway during infection in a high-glucose environment. This study provides evidence to support the use of insulin in the treatment of UPEC infection in patients with type 2 diabetes (T2D).